Rock ‘n’ Wall: Designing the Absence - Mancini, Francesco (2015)
How to question the role of the urban monument in the contemporary European city today? Challenging the generic concept of a city as a set of fundamental structures/infrastructures might lead to question urban identity beyond the evidence of urban forms' permanence over time.